A escolha da estratégia de entrada em mercados internacionais: estudo de casos no setor de distribuição de gás natural comprimido - Rabelo, Lúcia Mathias (2007)
Natural gas is a versatile fossil fuel that can be used for many applications. Because of its remarkable attributes its use is being encouraged by private and public sectors globally. It is an alternative to oil, a cheap commodity and environmentally friendly. The distribution of gas is technically difficult and demands long term, high density investments. One solution adopted to overcome some of these barriers and subject of this study is named as Compressed Natural Gas or CNG. This research aims to explore if there are drivers leading the internationalisation process of firms supplying equipment or services for CNG distribution and what are the different issues that may exert influence over it. Moreover, it intends to address a strategy for small firm s market entry holding this technical solution. Literature is divided in areas that may answer the main objectives. The topic of internationalization motives explains if this decision is reasonable to companies through the analysis of the drivers in this process. The second topic introduces the reader to the dynamic forces of international business, and explains how they influence the entry mode choice in an external market. Finally, the third part describes modes of entry; and the most relevant internationalisation models for this dissertation. The research strategy adopted is a case study. The cases investigated were the experience of Neogas entering Brazil and China markets, and Galileo entering foreign markets. Primary data was collected through interviews. In order to provide a background to the topic, further literature was sought concerning natural gas industry and the business environment in this sector in Brazil, in addition to CNG technology information. It was found out that CNG technology internationalisation drivers are directly related to natural gas drivers. Thus, while there are factors encouraging the utilization of natural gas globally, there are reasons to internationalise CNG. However, as an alternative to traditional distribution, it needs to focus on emergent markets with a lack of pipeline infrastructure and low cost natural gas. The entry mode choice depends mainly in the firm s strategy, resources available and internal and external production factors. A company commercialising CNG equipment or services needs to keep proximity to the external market. In addition to that, it should take advantage of the combination between entry modes band the variations among them. Businesses will rely on partnerships and close personal relationships to overcome small firm s limitations. Finally, it is concluded that international business is affected by constantly conflicting forces; and that the study of the intensity of these forces impact in businesses can be a topic for future research.